Effects of water ingestion throughout exercise and recovery on cardiac autonomic modulation during and after exercise - Moreno, Isadora Lessa; Vanderlei, Luiz Carlos Marques [UNESP]; Vanderlei, Franciele Marques [UNESP]; Pastre, Carlos Marcelo [UNESP]; Abreu, Luiz Carlos De; Ferreira, Celso (Universidade Estadual Paulista, 2016)
Purpose: To analyze the effects of water intake on heart rate variability (HRV) during and after exercise. Methods: Thirty-one young males performed three different procedures: I) a maximal exercise test to determine the load for the protocols; II) the control protocol (CP); III) the experimental protocol (EP). The protocols comprised 10 minutes at rest, 90 minutes of treadmill exercise (60% of VO2 peak), and 60 minutes of recovery. No rehydration beverage consumption was allowed during the CP. During the EP, the participants were given water every 15 minutes, being that the amount of water to be ingested by each volunteer was divided over the time of exercise and recovery. For the analysis of HRV data, time and frequency domain indices were investigated in the following moments (M): M1 (5 minutes final of rest), M2 (25-30 minutes of exercise), M3 (55-60 minutes of exercise), M4 (85-90 minutes of exercise), M5 (5-10 minutes of recovery), M6 (15-20 minutes of recovery), M7 (25-30 minutes of recovery), M8 (40-45 minutes of recovery), and M9 (55-60 minutes of recovery). Results: There was no statistically significant difference between the groups that were examined during the exercise. HRV values for the CP and EP at the end of the exercise period were as follows SDNN (5.95±1.89 vs 6.89±2.11); RMSSD (3.29±0.78 vs 3.39±0.95); HF [nu] (24.06±14.26 vs 19.10±11.94); LF [nu] (75.93±14.26 vs 80.89±11.94); HF [ms2] (0.90±1.16 vs 0.94±0.89); LF [ms2] (4.65±5.94 vs 5.35±5.09); and LF/HF ratio (4.64±3.15 vs 6.95±5.57). HRV values for the CP and the EP at the end of the recovery period were as follows: SDNN (39.63±19.63 vs 49.95±17.79); RMSSD (21.63±15.55 vs 36.43±22.73); HF [ms2] (285.51±392.27 vs 699.29±699.66); LF [nu] (74.55±13.25 vs 61.19±19.27); and HF [nu] (25.44±13.25 vs 38.8±19.27). Conclusion: The hydration with water was not enough to significantly influence the linear HRV indices during exercise; however, it promoted faster recovery of these variables after exercise.
Keywords: exercise; rehydration solutions; autonomic nervous system; heart rate